Mitochondria-associated regulation in adipose tissues and potential reagents for obesity intervention - Zheng, Yali; Yang, Ni; Pang, Yueshan; Gong, Yanju; Yang, Hong; Ding, Weijun; Yang, Hongya (Frontiers in Endocrinology, 2023)
Introduction A systematic review analysis was used to assess the profile of mitochondrial involvement in adipose tissue regulation and potential reagents to intervene in obesity through the mitochondrial pathway. Methods Three databases, PubMed, Web of Science, and Embase, were searched online for literature associated with mitochondria, obesity, white adipose tissue, and brown adipose tissue published from the time of their creation until June 22, 2022, and each paper was screened. Results 568 papers were identified, of which 134 papers met the initial selection criteria, 76 were selected after full-text review, and 6 were identified after additional searches. A full-text review of the included 82 papers was performed. Conclusion Mitochondria play a key role in adipose tissue metabolism and energy homeostasis, including as potential therapeutic agents for obesity.